2016
DOI: 10.1098/rspb.2016.0832
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of habitat, zooplankton, host stage structure and diversity on amphibian chytrid

Abstract: Why does the severity of parasite infection differ dramatically across habitats? This question remains challenging to answer because multiple correlated pathways drive disease. Here, we examined habitat-disease links through direct effects on parasites and indirect effects on parasite predators (zooplankton), host diversity and key life stages of hosts. We used a case study of amphibian hosts and the chytrid fungus, Batrachochytrium dendrobatidis, in a set of permanent and ephemeral alpine ponds. A field exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Up to date, no symptomatology or mortality due to Bd infection has been detected in the surveyed area. However, parasite infection differs dramatically across years and habitats, and severe epidemics occur infrequently and unpredictably in a relatively small subset of habitats (Hite et al, 2016). The study conducted by Hite et al (2016) found that the structure of habitat and the existence of permanent waterbodies were linked to the density of Bd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, no symptomatology or mortality due to Bd infection has been detected in the surveyed area. However, parasite infection differs dramatically across years and habitats, and severe epidemics occur infrequently and unpredictably in a relatively small subset of habitats (Hite et al, 2016). The study conducted by Hite et al (2016) found that the structure of habitat and the existence of permanent waterbodies were linked to the density of Bd.…”
Section: Discussionmentioning
confidence: 99%
“…However, parasite infection differs dramatically across years and habitats, and severe epidemics occur infrequently and unpredictably in a relatively small subset of habitats (Hite et al, 2016). The study conducted by Hite et al (2016) found that the structure of habitat and the existence of permanent waterbodies were linked to the density of Bd. Our results show great differences among populations, possibly caused by important differences in structure among ephemeral or temporary ponds.…”
Section: Discussionmentioning
confidence: 99%
“…The zooplankton are also more appropriate regulators of Bd abundance than is X . laevis larvae because they are native to most aquatic systems and have been shown to potentially reduce Bd abundance through predation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bd transmission occurs through a motile zoospore stage that swims through the water to infect a new host or re-infect the current host. Zooplankton, such as Daphnia [ 6 , 7 , 12 , 13 ] and ciliates [ 14 ], consume the motile zoospore stage of Bd from the water column. The reduction of Bd zoospores may lead to reduced transmission rates to amphibians in the water [ 7 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chytridiomycosis in the Spanish Central Range negatively affects the population-level dynamics of several amphibian species. The variability of its effects has been associated with water temperature variability (Fernandez-Beaskoetxea et al, 2015) and UV-B exposure (Ortíz-Santaliestra et al, 2011;Hite et al, 2016). However, the relationship between the presence of Bd and abiotic factors is not always clear, and the relationship between environmental variables and the prevalence of the infections is weak (Walker et al, 2010).…”
Section: Bdmentioning
confidence: 99%